Exploring the Diversity and Antimicrobial Potential of Marine Actinobacteria from the Comau Fjord in Northern Patagonia, Chile - Undabarrena, Agustina; Beltrametti, Fabrizio; Claverías, Fernanda P.; González, Myriam; Moore, Edward R. B.; Seeger, Michael; Cámara, Beatriz (Frontiers in Microbiology, 2016)
Bioprospecting natural products in marine bacteria from fjord environments are attractive due to their unique geographical features. Although Actinobacteria are well known for producing a myriad of bioactive compounds, investigations regarding fjord-derived marine Actinobacteria are scarce. In this study, the diversity and biotechnological potential of Actinobacteria isolated from marine sediments within the Comau fjord, in Northern Chilean Patagonia, were assessed by culture-based approaches. The 16S rRNA gene sequences revealed that members phylogenetically related to the Micrococcaceae, Dermabacteraceae, Brevibacteriaceae, Corynebacteriaceae, Microbacteriaceae, Dietziaceae, Nocardiaceae and Streptomycetaceae families were present at the Comau fjord. A high diversity of cultivable Actinobacteria (10 genera) was retrieved by using only five different isolation media. Four isolates belonging to Arthrobacter, Brevibacterium, Corynebacterium and Kocuria genera showed 16S rRNA gene identity <98.7% suggesting that they are novel species. Physiological features such as salt tolerance, artificial sea water requirement, growth temperature, pigmentation and antimicrobial activity were evaluated. Arthrobacter, Brachybacterium, Curtobacterium, Rhodococcus and Streptomyces isolates showed strong inhibition against both Gram-negative Pseudomonas aeruginosa, Escherichia coli and Salmonella enterica and Gram-positive Staphylococcus aureus, Listeria monocytogenes. Antimicrobial activities in Brachybacterium, Curtobacterium and Rhodococcus have been scarcely reported, suggesting that non-mycelial strains are a suitable source of bioactive compounds. In addition, all strains bear at least one of the biosynthetic genes coding for NRPS (91%), PKS I (18%) and PKS II (73%).Our results indicate that the Comau fjord is a promising source of novel Actinobacteria with biotechnological potential for producing biologically active compounds.